EXPERIENCE OF FOREIGN COUNTRIES IN SUICIDE PREVENTION - Niyozova Salomat Saparovna (PT. Antis International Publisher, 2024)
General Background: Suicide remains a pressing global health issue, prompting extensive research into effective prevention strategies across diverse cultural contexts. Specific Background: This article delves into international practices in suicide prevention, highlighting the complexities of victimization in different countries. It emphasizes the need to understand the interplay between societal factors and individual behaviors in mitigating suicide risks. Knowledge Gap: Despite the wealth of studies on suicide prevention, there is a paucity of research specifically addressing the concept of victimology as it pertains to suicide, particularly regarding the behavioral modifications that can shield individuals from becoming victims of suicidal ideation and actions. Aims: This study aims to fill this gap by exploring how victimology principles can inform suicide prevention strategies, thereby enhancing awareness of criminal dangers associated with suicide and promoting behavior changes that lower victimization risks. Results: The analysis reveals that effective suicide prevention interventions often incorporate victimology concepts, suggesting that educating individuals about potential risks and adaptive behaviors can significantly reduce suicide rates. Novelty: This article introduces a novel perspective by integrating victimology into the discourse on suicide prevention, advocating for a paradigm shift in how we understand and address this critical issue. Implications: The findings underscore the importance of interdisciplinary approaches in suicide prevention, recommending that policymakers and practitioners incorporate victimology insights into their strategies to enhance overall efficacy and reduce the incidence of suicide globally.